Konsep Dasar Mengenai Teori Belajar Kognitif Serta Tahapannya Menurut Para Ahli dan Implikasinya Didalam Pembelajaran - Zikrulloh, Muhamad; Srihartini, Yusi; Humairo, Shovi Sholahiyah; Yulistiani, Siti Alfiah (At-Tadris: Journal of Islamic Education, 2025)
Cognitive learning theory is an approach in educational psychology that emphasizes the importance of mental processes in understanding, storing and remembering information. The basic concept of this theory relies on how individuals construct knowledge through interaction with the environment, experience, and information processing. Experts such as Jean Piaget, Lev Vygotsky, and Jerome Bruner made significant contributions to the development of this theory. Piaget introduced stages of cognitive development, including sensorimotor, preoperational, concrete operational, and formal operational. Vygotsky emphasized the importance of social interaction and the concept of the zone of proximal development (ZPD), while Bruner introduced the learning theory of discovery learning. The implications of cognitive learning theory in learning include the importance of providing meaningful learning experiences, using learning media that stimulate information processing, as well as adapting teaching materials according to students' stages of cognitive development. This approach also encourages exploration-based learning, collaboration, and strengthening critical thinking skills.